Pengaruh Kepemimpinan Kepala Sekolah, Motivasi Dan Pelatihan Terhadap Kinerja Guru SMAN 1 Mambi Kabupaten Mamasa - Adriani B; Nurdin Latif; Ansar Taufik (STIM-LPI Makassar, 2023)
This study aims to determine and prove the influence of the principal's leadership on teacher performance at State Senior High School 1 Mambi, Mamasa Regency, to find out and prove the effect of motivation on teacher performance at State High School 1 Mambi, Mamasa Regency, to find out and prove the effect of training on teacher performance. State Senior High School 1 Mambi, Mamasa Regency, to find out and prove the influence of the principal's leadership, motivation and training on teacher performance at State High School 1 Mambi, Mamasa Regency. Data collection is done through documentation, observation, and questionnaires. The teacher sample is 28 respondents. Data processing consisted of descriptive analysis, correlation analysis and regression analysis. The results showed that with a significant level of 5% and degrees of freedom df1 = 3 and df2 = 24, f table was obtained (3:24) = 3.009. Based on the ANOVA test or F test from the SPSS output, it can be seen that the f count is 17,719 > 3.009 the f table value and the probability is 0.000 <0.05. More precisely, the calculated F value is compared to the F table where if F count > F table then simultaneously leadership, motivation and training have a positive and significant effect on teacher performance at SMA Negeri 1 Mambi, Mamasa Regency. This means that the hypothesis of the two researchers is accepted.